RELATIVE EFFICIENCIES OF DIFFERENT LIPIDS AND LIPID LEVELS IN THE DIET OF THE PRAWN PENAEUS INDICUS - Ali, S Ahmad (Indian Journal of Fisheries, 2011)
Among the four lipids, cod liver oil, prawn head oil, sardine oil and soybean lecithin, tested at 6% level in a purified diet, for the prawn Penaeus indicus, the diets having prawn head oil and a mixed lipid consisting of all the four lipids in equal proportions, showed significantly (P<0.01) higher growth and the best food conversion ratio (FCR). These wore followed by the diets having soybean lecithin, sardine oil and cod liver oil in the decreasing order. Investigations on the effect of lipid level in the diet on the growth, FCR and survival of the prawn have shown that the diet having 6% lipid produced significantly higher growth (P<0.01), best FCR and high survival rate. While the growth, FCR and survival of the prawns fed with the diets having less than 6% lipid, were poor, the animals fed with the diets having higher lipid levels did not show any improvement. Using a mixed lipid and carbohydrate (starch) in the ratio 1:7, the calorific value of the diet was varied from 271.68 Kcal/100 g to 462. 43 Kcal/100 g, keeping the protein constant. Feeding experiments conducted with these diets have shown that the growth of prawns increased and the FCR improved with increase in the dietary energy. The diet having 414.72 Kcal/100 g recorded the highest growth and the best FCR, while further increase in the calorific value of the diet had no beneficial effect on the growth and FCR of the prawns. The significance of qualitative and quantitative lipid requirements of prawns in relation to the calorific value of the diet is discussed.